Integrating Community Satisfaction Survey and Importance-Performance Analysis for Evaluating Regional Tourism Services: A Case Study in Banyuwangi Regency - Kurniawan , Astariadi; Resyah, Nur Isra; Windawaty , Herry Windawaty; Habibie , Muhammad (CV. Science Tech Group, 2025)
This study explores the integration of the Community Satisfaction Index (CSI) and Importance–Performance Analysis (IPA) to evaluate public service quality in Banyuwangi's tourism sector. As tourism becomes a regional development priority post-pandemic, understanding citizens' perceptions is essential to ensure responsive governance. Using a quantitative-descriptive approach, the research draws on 2023 data from tourists and tourism actors. Results indicated an overall satisfaction score of 82.94 (“Good”), with highest satisfaction in staff behavior and lowest in complaint handling. IPA mapping identifies critical gaps in services such as accessibility, transportation, and complaint response, highlighting areas for urgent policy action. The integration of IKM and IPA proves effective in prioritizing service improvements and aligning tourism development with citizen needs. Comparative insights with global practices affirm the relevance of participatory, data-driven evaluation frameworks. The study recommends institutionalizing IKM+IPA for sustainable tourism governance.